The degree to which English teachers use the techniques of education in the second cycle of basic education from their point of view. "A Field Study in Lattakia City Schools" (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The aim of the research was to identify the degree of use of the teaching techniques of English teachers in the second cycle of basic education in the Lattakia schools. To achieve the goal of the research, the researcher applied a questionnaire containing (26) items addressed to the teachers of the English language, and verified its validity and stability, (30) teachers, and the results of the research showed that the second area (educational aids) obtained a great degree, where the educational average (3.11), while the rest of the areas to a middle degree, and ranged between educational levels (2.54 - 2.90 ), Thus becoming the grade average for the instrument's total score (2.7), which is Z Fiber in general. The results of the first question showed that the degree of use of English teachers for teaching techniques was weak. The educational average of the overall score of performance was (2.7) which is weak. The results also showed that there were no statistically significant differences between the average of the sample members' For the gender variable, according to the variable of scientific qualification. The results also showed that there were no statistically significant differences between the average estimates of the members of the research sample on the total degree of the tool and its sub-dimensions according to thevariable years of experience.